INTEGRATION OF A COOKING EDUCATIONAL WEBSITE INTO PRIMARY SCHOOL EDUCATION - Mirzarakhimova Farangiz Akmaljonovna,; Zakirova Feruza Makhmudovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article discusses the use of an educational cooking website in primary school education. The main aim of the study is to show how a digital platform can help children learn simple cooking skills and develop useful everyday abilities. The website allows pupils to watch videos, follow step-by-step instructions, and complete interactive tasks. It can be used during classroom lessons and extracurricular activities. The article explains that digital tools make learning more interesting and practical for children. As a result, functional literacy, independence, and responsibility can be developed from an early age. The study proves that cooking websites are not only entertaining but also educational and useful for personal development.